Essays on the Modern Japanese Church Christianity in Meiji Japan - Yamaji, Aizan (Michigan Monograph Series in Japanese Studies, 2020)
Essays on the Modern Japanese Church (Gendai Nihon kyokai shiron), published in 1906, was the first Japanese-language history of Christianity in Meiji Japan. Yamaji Aizan's firsthand account describes the reintroduction of Christianity to Japan-its development, rapid expansion, and decline-and its place in the social, political, and intellectual life of the Meiji period. Yamaji's overall argument is that Christianity played a crucial role in shaping the growth and development of modern Japan.